Pengaruh Harga Terhadap Kepuasan Pelanggan MR.DIY Pada Mahasiswa Program Study Manajemen, Universitas Negeri Medan - Rexsy Mardohot Sitanggang; Nabila Boru Lubis; Nabila Umaira; Novia Grace Limbong; M. Rayhan Satria; Nurul Wardani Lubis (JIM UPB (Jurnal Ilmiah Manajemen Universitas Putera Batam), 2025)
This study examines the effect of price on customer satisfaction among Management Program students at the State University of Medan who shop at MR.DIY. Using a quantitative design with convenience sampling, data were collected from 100 respondents through questionnaires and analyzed using IBM SPSS Statistics 26. The results of validity, reliability, and normality tests confirmed that the instrument was appropriate for analysis. Simple linear regression showed a positive and significant effect of price on customer satisfaction, with a regression coefficient of 0.634 and a significance value of 0.001 (p < 0.05). The coefficient of determination (R²) of 0.617 indicates that price explains 61.7% of the variance in customer satisfaction. These findings highlight the importance of aligning pricing strategies with students’ purchasing capacity to enhance satisfaction and support long-term customer loyalty